ASSOCIATION BETWEEN SAFETY CLIMATE AND NURSING WORKLOAD - Verusca Soares de Souza; João Lucas Campos de Oliveira; Maria Antônia Ramos Costa; Grazieli de Vicente; Renata Rodrigues Mendonça; Laura Misue Matsuda (Universidade Federal do Paraná, 2019)
Objective: To verify the association between safety climate and the workload of nursing professionals of an Intensive Care Unit.Method: Cross-sectional analytical study, with data collected from June to October 2014, in a public hospital in the state of Paraná. The Safety Attitudes Questionnaire (SAQ) and Nursing Activities Score (NAS) instruments were used. The median of the unit's Nursing Activities Score (571 points) was used as cutoff point, and the scores of the Safety Attitudes Questionnaire were dichotomized among professionals under high workload (> 571 points). Results: An association between three domains of the SAQ: teamwork climate (p = 0.010), safety climate (p = 0.009) and job satisfaction (p-value 0.020) was obtained.Conclusion: The findings of this study can serve as a basis for actions aimed at improving working conditions and, consequently, job satisfaction and quality of care.